Determination of Methods to Assess Genetic Variation in the MHC DQB locus of the Florida Manatee, Trichechus manatus latirostris - Schwam, Aimee (My University, 2010)
Research involving the endangered Florida manatee attempts to find ways to manage the population. The Major Histocompatibility Complex (MHC) group of genes is important in eliciting the mammalian immune response. In this study, I determined the number of clones necessary to assess the number of class II MHC DQB alleles in an individual manatee. During the course of the study. I ascertained that the scraping method used for collecting tissue was not ideal for obtaining the pure DNA needed for an examination of 500 nucleotides of the MHC DQB region. MHC variability was assessed by sequencing clones of an approximately 200 base-pair long region of the gene. The results indicate that approximately 10 clones are necessary to determine whether an individual is homozygous or heterozygous. There was only one variable nucleotide in the sequenced region, suggesting that future studies may find low genetic diversity at this locus in the population.